Polyploid giant cancer cells: Unrecognized actuators of tumorigenesis, metastasis, and resistance. Issue 13 (2nd August 2019) - Amend, Sarah R.; Torga, Gonzalo; Lin, Ke‐Chih; Kostecka, Laurie G.; de Marzo, Angelo; Austin, Robert H.; Pienta, Kenneth J.
Abstract : Cancer led to the deaths of more than 9 million people worldwide in 2018, and most of these deaths were due to metastatic tumor burden. While in most cases, we still do not know why cancer is lethal, we know that a total tumor burden of 1 kg—equivalent to one trillion cells—is not compatible with life. While localized disease is curable through surgical removal or radiation, once cancer has spread, it is largely incurable. The inability to cure metastatic cancer lies, at least in part, to the fact that cancer is resistant to all known compounds and anticancer drugs. The source of this resistance remains undefined. In fact, the vast majority of metastatic cancers are resistant to all currently available anticancer therapies, including chemotherapy, hormone therapy, immunotherapy, and systemic radiation. Thus, despite decades—even centuries—of research, metastatic cancer remains lethal and incurable. We present historical and contemporary evidence that the key actuators of this process—of tumorigenesis, metastasis, and therapy resistance—are polyploid giant cancer cells.